2016
DOI: 10.1016/j.jdiacomp.2015.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of advanced glycation end products in the DHS Mind Study

Abstract: Aims Human studies of links between advanced glycation end-products (AGEs) and disease phenotypes are less common than studies of animal and cell models. Here, we examined the association of total AGEs with diabetes risk factors in a predominately type 2 diabetes (T2D) affected cohort. Methods AGEs were measured using an enzyme linked immunosorbant assay in 816 individuals from the DHS Mind Study (n=709 T2D affected), and association analyses were completed. Results Total AGEs were associated with estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
0
3
0
2
Order By: Relevance
“…The incidence of cognitive impairment was higher in those with high or mid pentosidine levels than those in the lowest tercile (odds ratio = 1.55; 95% CI: 1.07-2.26). Similarly, circulating AGEs have been associated with poorer cognitive performance on the digit substitution test in a cohort of people predominantly diagnosed with T2DM [114]. In the same study, decreased grey matter volume was also observed in people without T2DM with higher AGE consumption.…”
Section: Ages and Neurocognitive Disordersmentioning
confidence: 61%
See 1 more Smart Citation
“…The incidence of cognitive impairment was higher in those with high or mid pentosidine levels than those in the lowest tercile (odds ratio = 1.55; 95% CI: 1.07-2.26). Similarly, circulating AGEs have been associated with poorer cognitive performance on the digit substitution test in a cohort of people predominantly diagnosed with T2DM [114]. In the same study, decreased grey matter volume was also observed in people without T2DM with higher AGE consumption.…”
Section: Ages and Neurocognitive Disordersmentioning
confidence: 61%
“…Several studies have investigated the association of circulating and tissue AGE levels with cognition [18,[114][115][116][117][118][119][120]. Most studies focused on blood AGEs, rather than dietary AGEs or interventions that modify dietary AGEs.…”
Section: Ages and Neurocognitive Disordersmentioning
confidence: 99%
“…As for variants of MT1A, significant association of rs964372 exists with diabetic neuropathy (linked to hyperlipidemia) [60] (as for MT2A, see below). More recently, rs7198427 and rs7197489, initially attributed to the MT1A gene portion, were identified by genome-wide association study (GWAS) as associated to advanced glycation endproducts (AGEs) in diabetic subjects [62].…”
Section: Mt1a Polymorphismsmentioning
confidence: 99%
“…Крім того, було продемонстровано, що ПДГ, депоновані в інтерстиції і стінках судин, корелюють з розвитком фіброзу, транспортною характеристикою мембрани, рівнем ультрафільтрації та кардіоваскулярною смертністю [24,25]. Формуванню ПДГ сприяє уремія, цукровий діабет, та інші дегенеративні захворювання, які асоційовані зі збільшенням молекулярного субстрату та оксидативним стресом [4,27].…”
unclassified